Strategic decision analysis: Applied decision analysis and its role in the strategic management process - Thomas, Howard (Institutional Knowledge at Singapore Management University, 1984)
This paper examines a role for applied decision analysis in the strategic management process. It is argued that decision analysis should be regarded both as a heuristic and a ‘thinking’ algorithm for decision structuring and problem diagnosis and, in addition, as an input to the process of policy dialogue. A policy dialogue paradigm using decision analysis is outlined, in which various viewpoints are reconciled by the questioning of analyses and assumptions. This dialogue paradigm is viewed as being compatible with approaches such as strategic assumptions analysis, which have been suggested in the literature as an aid for the processes of problem finding, formulation and solution.